Geochemistry Examination of Surface Sediments from Sadong River, Sarawak, Malaysia: Validation of ICP-OES Assessment of Selected Heavy Metals Selected Heavy Metals - Zaini, Bin Assim; Rafeah, Binti Wahi; Asare, Ebenezer Aquisman; Droepenu, Eric Kwabena; Durumin Iya, Naseer Inuwa (Society for Innovative Research (SIR), 2019)
The dependable analytical method for the assessment of heavy metals of interest (As, Al, Mn, Ca, Cd, Cu, Fe, Cr, Ni, Co, Zn and Pb) in sediments assembled in the Sadong River, Sarawak state of Malaysia was reported. The total acid digestion extraction proceeded by ICP-OES (Inductively Coupled Plasma - Optical Emission Spectrometry) was used for this reason. The analytical method was validated as well as the implementation of enough quality control activities in order to supply reliable information. Duplicate analysis was estimated in order to achieve the precision reproducibility conditions. To determine the accuracy of the results certified reference material was used. The limits of detection and quantification for all selected metals were below the acceptable limits in the examined sediment samples. The acquired dependable information could be used for evaluations of the correlation between anthropogenic activity in the aged and the geochemical characteristics of the sediments.